Serum exosomal and serum glypican-1 are associated with early recurrence of pancreatic ductal adenocarcinoma - Zhao, Juan; Guo, Madi; Song, Yushuai; Liu, Shan; Liao, Ran; Zhang, Yu; Zhang, Yumin; Yang, Qi; Gu, Yuanlong; Huang, Xiaoyi (Frontiers in Oncology, 2022)
Background: The diagnostic performance and prognostic value of serum exosomal glypican 1 (GPC-1) in pancreatic ductal adenocarcinoma (PDAC) remain controversial. In this study, we detected serum exosomal GPC-1 using enzyme-linked immunosorbent assay (ELISA) and determined whether it serves as a predictor of diagnosis and recurrence for early-stage PDAC. Methods: Serum samples were obtained from patients with PDAC, benign pancreatic tumor (BPT), or chronic pancreatitis (CP) and healthy controls (HCs). Serum exosomes were isolated using an exosome isolation kit. Exosomal and serum GPC-1 levels were measured using ELISA. The freeze–thaw process was carried out to analyze the stability of GPC-1. Receiver operating characteristic (ROC) analysis was employed to assess the diagnostic value of GPC-1. Kaplan–Meier and multivariate Cox analyses were used to evaluate the prognostic value of GPC-1. Results: The average concentrations of serum exosomal and serum GPC-1 were 1.45 and 0.80 ng/ml, respectively. GPC-1 expression levels were stable under repeated freezing and thawing (d1-5 freeze–thaw cycles vs. d0 P > 0.05). Serum exosomal and serum GPC-1 were significantly elevated in patients with PDAC compared with HCs (P < 0.0001) but were slightly higher compared with that in patients with CP and BPT (P > 0.05). The expression levels of exosomal and serum GPC-1 were elevated 5 days after surgery in patients with PDAC, CP, and BPT (P < 0.05). Patients with high levels of exosomal and serum GPC-1 had a shorter relapse-free survival (RFS) (P = 0.006, and P = 0.01). Multivariate analyses showed that exosomal and serum GPC-1 were independent prognostic indicators for early RFS (P = 0.009, and P = 0.031). Conclusion: ELISA is an effective and sensitive method to detect exosomal and serum GPC-1. The detection of GPC-1 was stable under repeated freezing and thawing cycles and could distinguish early-stage PDAC from HC but not CP and BPT. Exosomal and serum GPC-1 may be good independent predictors of early recurrence in early-stage PDAC.